Sistem Pendukung Keputusan Pemilihan Peserta Jaminan Kesehatan Masyarakat (Jamkesmas) Menerapkan Metode MOORA - Mesran Mesran; Swandi Dedi Arnold Pardede; Arahman Harahap; Andysah Putera Utama Siahaan (STMIK Budi Darma, 2018)
Decision support system as a computer-based system consisting of components, among other components of the language system (language), components of knowledge systems (knowledge) and components of the problem processing system (problem processing) which interact with each other, which helps decision making through the use of data and decision models to solve problems that are semi-structured and unstructured. This study uses the MOORA Method in determining who is entitled to become participants Jamkesmas based on criteria by using a formula that results more accurate and targeted.